(untitled) (The Review of Diabetic Studies, 2025)
Background: Burns are a common type of injury that can cause significant tissue damage and pose a threat to life. Aim: The aim is to evaluate a comprehensive protocol for managing critically ill burn patients who also have significant medical comorbidities, by integrating advanced imaging and laboratory diagnostics with evidence-based clinical pathways. Material and method: A retrospective single-center study was performed in a hospital with 40 adult burn patients who had severe burns (>10% TBSA) and at least one serious comorbidity. The study encompassed expedited clinical evaluations of burn dimensions, depth, airway condition, and particular laboratory analyses. Caring tactics included stabilizing critical care patients by managing their airways and carefully giving them fluids, as well as enlisting many different healthcare personnel in their care. Ongoing care included daily team meetings, serial laboratory tests, and help with mental health issues. The main outcomes were wound healing, infection rates, and how long patients were in the ICU. The secondary outcomes were pain, mobility, quality of life, and death. Results: The research indicated that the intervention and control groups were demographically comparable, confirming that result disparities were attributable to the intervention. The intervention group showed big drops in inflammatory cytokines (TNF-α, IL-17, IL-10, IL-6), which shows that the inflammation was effectively modulated. Key indicators of angiogenesis and fibrosis (VEGF, TGF-β) diminished following therapy in the intervention group, indicating a reduction in pathological responses during burn healing. Conclusion: This study confirms that a comprehensive strategy integrating laboratory diagnoses and treatment interventions significantly improves outcomes for critically ill burn patients with comorbidities.